Neighbourhood negotiations: network governance in post-Katrina New Orleans - Danley, S (2013)
This inquiry into informal networks and policy negotiations is set in the theoretical framework of network governance. It builds theory to explain informal networks by examining neighbourhood associations in post-Katrina New Orleans through a variety of qualitative methodologies including interviews, document analysis, surveying and ethnography. In New Orleans, neighbourhood associations do not engage in social-service delivery, they prioritise neighbourhood protection and neighbourhood change. They represent their neighbourhoods through a system of intensive volunteering not elections. That system burns out neighbourhood leaders and leaves associations constantly looking for new volunteers. These associations partner with non-profits, work with politicians, and engage in fierce conflict when excluded from policy negotiations. Finally, they set their agenda based upon the physical characteristics of their neighbourhoods, investing in local institutions. These findings contribute to network governance theory. New Orleans’ democracy of volunteers introduces a new form of democratic anchorage to governance theory. Actors in informal networks have varying priorities. This demonstrates the importance of early involvement by these actors in policy creation and the ways in which policy construction can ignore community. Neighbourhood associations blackmail, bribe and coerce to create their own power, showing how power at the micro-level includes not only resources and decision-making, but also interest. These findings fit into a broader theme. Negotiations with multiple actors improve policy by incorporating complex priorities and neighbourhood context into the policy system. This wider theme of how to address complexity is the policy equivalent of the wisdom of crowds. Policy-makers can either incorporate complexity such as local context and differing priorities or face the conflict and consequences of ignoring it.